The Relationship Between Cognitive Function And Stroke Severity In Bethesda Hospital, Yogyakarta - Pinzon, Rizaldy Taslim; Marpaung, Refianda Olivia Febrianti; Sugianto (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Stroke is a clinical manifestation of impaired brain function, both focally and globally, which can be severe and last for 24 hours. Damage to brain cells can cause cognitive, sensory and motoric dysfunction and hinder functional abilities from daily activities to communication caused by brain cells in stroke patients. Aims this study to determine the relationship between cognitive function and stroke severity at Bethesda Hospital, Yogyakarta. Methods: This study used a retrospective cohort method in 118 ischemic stroke patients with mild to moderate levels of cognitive function within 1-3 months after the first attack using secondary stroke registry. The patient's cognitive function was measured by the MMSE when the patient was discharged from hospital and stroke severity was measured by the NIHSS when the patient was first admitted to the hospital. Results: Of the 118 patients, the majority of patients in this study were male (59.3%), aged â‰¥ 60 years (57.6%). In this study, no significant relationship was found between cognitive function and stroke severity (p = 0.106). Gender, age, history of hypertension, history of diabetes mellitus, history of dyslipidemia, and the patient's education level did not find a significant association with cognitive function as assessed by the MMSE score and the severity of stroke as assessed by the NIHSS score. Conclusion: There was no significant relationship between cognitive function as assessed by the MMSE score and stroke severity as assessed by the NIHSS score. Keywords: Cognitive function, Stroke severity, Stroke, MMSE, NIHSS, Disability.